I heart design : remarkable graphic design selected by designers, illustrators, and critics - Heller, Steven (Rockport Publishers, 2011)
This is a collection of 'favourite' designs as selected by 80 prominent graphic designers, typographers, teachers, scholars, writers and design impresarios. Designs featured include the iconic CBS eye, the stark Kodak identity, the Coca-Cola bottle, and, of course, The Rolling Stones' Sticky Fingers album cover.